DAYA SAING TEKNOLOGI DESTINASI PARIWISATA DKI JAKARTA BERDASARKAN PERSEPSI WISATAWAN - Nurbaeti, Nurbaeti; Damanik, Janianton; Baiquni, Muhammad; Nopirin, Nopirin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2015)
This study aims to examine and analyze the use of technology in improving the competitiveness of the tourism destination based on tourists’ perception, and also to see the difference level of technology competitiveness. This research has been conducted specifically to analyse the technology competitiveness at the three main tourist destinations mentioned above based on the visitors’s perception, and why the perception could be different. This study is a survey research which explains social phenomena and causal relationship among the variables of socio-economic characteristics (group of origin, level of education, and and income level) towards the competitiveness of technology parameter in the three tourist destination through hypothesis testing. Information was collected from 300 respondents using the questionnaire, and for each tourist destination, for the-100 respondent, the unit analyzed are individuals (tourists). Sample are tourists to the three main destinations in Jakarta during May, August, and September 2014. The selected samples are those who have visited the three different tourist destination within the last three years whose age are 15 years or more. The collected data were then analyzed using Kruskall-Walls statistical test, i.e. nonparametric analysis instrument to see whether there are any difference between two conditions. Based on group of origin, level of education, and income level of the respondents, the results showed have no differences in perception to technology competitiveness of the three tourist destinations. Keywords: tourist destination, tourists’ perception, tourism destination competitiveness